2020
DOI: 10.1007/s40145-020-0376-7
|View full text |Cite
|
Sign up to set email alerts
|

Controllable fabrication and multifunctional applications of graphene/ceramic composites

Abstract: Graphene with excellent comprehensive properties has been considered as a promising filler to reinforce ceramics. While numerous studies have been devoted to the improvement of mechanical and electrical properties, incorporating graphene to ceramics also offers new opportunities for endowing ceramics with versatility. In this review, the recent development of graphene/ceramic bulk composites is summarized with the focus on the construction of well-designed architecture and the realization of multifunctional ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 135 publications
0
50
0
Order By: Relevance
“…Particularly, graphene has received special attention due to its low density, high specific surface area, strong dielectric loss, and high electronic conductivity. However, to address the interfacial impedance mismatching of single graphene materials, ceramic/graphene composites have been broadly considered [ 189 , 190 ]; among the factors affecting their EMI shielding are the absorber type and content, thickness, and preparation method. For practical applications of ceramic/graphene composites, the main objective is to achieve good EM performance (including wide effective bandwidth, low reflection coefficient (RC) or large SE, and high-temperature stability) with minimum filler content and the tiniest thickness.…”
Section: Ceramic/graphene Composites For Electromagnetic Interference Shieldingmentioning
confidence: 99%
“…Particularly, graphene has received special attention due to its low density, high specific surface area, strong dielectric loss, and high electronic conductivity. However, to address the interfacial impedance mismatching of single graphene materials, ceramic/graphene composites have been broadly considered [ 189 , 190 ]; among the factors affecting their EMI shielding are the absorber type and content, thickness, and preparation method. For practical applications of ceramic/graphene composites, the main objective is to achieve good EM performance (including wide effective bandwidth, low reflection coefficient (RC) or large SE, and high-temperature stability) with minimum filler content and the tiniest thickness.…”
Section: Ceramic/graphene Composites For Electromagnetic Interference Shieldingmentioning
confidence: 99%
“…Graphene and its derivatives have strong absorbance in NIR range, high photothermal conversion efficiency and low toxicity in vivo, which are considered as a class of photothermal agents for potential photothermal tumor therapy. [90][91][92][93] Nowadays, many studies attempted to functionalize biomaterial scaffolds with graphene or its derivatives for achieving photothermal effect to combat bone tumors. For example, Ma et al used hBMSCs, pre-osteoblastic MC3T3-E1 cells and human osteosarcoma cells (HOS) as cell models, and found that nHA/GO particles exhibited good biocompatibility and excellent photothermal effect for killing HOS, and stimulating cell proliferation and differentiation of hBMSCs.…”
Section: Biomaterials Scaffolds With Hyperthermia Tumor Therapy and Bomentioning
confidence: 99%
“…Graphene and its derivatives have strong absorbance in NIR range, high photothermal conversion efficiency and low toxicity in vivo, which are considered as a class of photothermal agents for potential photothermal tumor therapy. [ 90–93 ] Nowadays, many studies attempted to functionalize biomaterial scaffolds with graphene or its derivatives for achieving photothermal effect to combat bone tumors. For example, Ma et al.…”
Section: Biomaterials Scaffolds With Hyperthermia Tumor Therapy and Bomentioning
confidence: 99%
“…The stability and security of electronic devices operating in the vicinity of the strong electromagnetic field are not guaranteed. Consequently, EMI shielding has been highly appreciated in civil, military and aerospace applications to ensure the security of electronic devices 1–8 . In the harsh environments where high strength and corrosion resistance are required, some widely used EMI shielding materials (eg, polymer and metal‐based composites) will lose their superiority, while ceramic materials exhibit excellent stability.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, EMI shielding has been highly appreciated in civil, military and aerospace applications to ensure the security of electronic devices. [1][2][3][4][5][6][7][8] In the harsh environments where high strength and corrosion resistance are required, some widely used EMI shielding materials (eg, polymer and metal-based composites) will lose their superiority, while ceramic materials exhibit excellent stability. Among those materials, oxide ceramic materials have many advantages to be used in the severe service environment, such as excellent mechanical properties and corrosion resistance, low cost, and nontoxicity.…”
Section: Introductionmentioning
confidence: 99%